Incubation and Innovation Design As A Potential Development Effort for Palembang City - Citra Istighotsah; Fuji Nurhasanah (International Journal of Regional Innovation, 2022)
This research is about the Innovation Incubation of Palembang City. Where, decentralization or regional autonomy has provided opportunities for local governments with their authority to try to strengthen public services in favor of the public interest. This research is considered important because incubation is a very important issue in determining the success of an area. The population in this study are areas that carry out incubation and innovation by utilizing their potential. While the subject in this study is the city of Palembang. The results of this study indicate that the activity of preparing the incubation and innovation plan for the City of Palembang is carried out through a series of activities, namely, the preparation of identification of regional potentials, the preparation of the incubation program, the preparation of the social and digital innovation program and the formulation of activities and action plans. The Government of Palembang City received two awards from the Ministry of Home Affairs as a Very Innovative City at the Innovative Government Award and the Ministry of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia (Kemen PANRB RI). Namely the award for Top 45 Public Service Innovations 2020. In addition, with the emergence of an integrated innovation ecosystem, regions can make facilities to improve community welfare through public service facilities, empowerment and community participation, and increasing regional competitiveness.